Longterm Survival and Cost‐Effectiveness of Immunosuppression Withdrawal After Liver Transplantation. Issue 9 (24th September 2018) - Manzia, Tommaso Maria; Angelico, Roberta; Toti, Luca; Angelico, Cristina; Quaranta, Claudia; Parente, Alessandro; Blasi, Francesca; Iesari, Samuele; Sforza, Daniele; Baiocchi, Leonardo; Lerut, Jan; Tisone, Giuseppe
Abstract : Lifelong immunosuppression (IS) after liver transplantation is associated with severe adverse effects and increased recipients' morbidity and mortality. Clinical operational tolerance has been reported in up to 40% in very well‐selected recipients. Longterm survival and cost savings within the Italian national health system in operational tolerant recipients is reported. Seventy‐five liver recipients were enrolled for IS withdrawal at our institution during the period from April 1998 to December 2015. The study population comprised 32 (42.7%) tolerant patients; 41 (54.7%) nontolerant patients needing uptake of IS after clinical or biopsy‐proven rejection; and 2 (2.7%) immediate nontolerant patients who developed early rejection after the first drug reduction. The primary endpoint of the study was to assess the longterm patients and graft outcome; the secondary endpoint was the assessment of cost savings in the context of IS withdrawal. The follow‐up was 95.0 months (interquartile range, 22.5‐108.5 months). IS withdrawal did not result in patient nor graft loss and resulted in a major cost savings reaching about €630, 000. In conclusion, longterm IS withdrawal represents a remarkable cost savings in the health care of liver recipients without exposing them to graft loss.